2009
DOI: 10.1159/000227816
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Potential of the Murine Embryonic Stem Cells Transplanted into the Healthy Rat Brain - Novel Insights into Tumorigenesis

Abstract: Although engraftment of undifferentiated pluripotent embryonic stem cells (ESCs) into the injured central nervous system (CNS) may lead to targeted cell replacement of lost/damaged cells, sustained proliferative activity combined with uncontrolled differentiation of implanted cells presents a risk of tumor formation. As tumorigenic potential is thought to be associated with pluripotency of embryonic stem cells, pre-differentiation may circumvent this problem. Recently, it has been demonstrated that tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Macrophage infiltration was shown to be less pronounced when stem cells were implanted into completely intact healthy brains. We therefore suggested that the massive macrophage infiltration at graft sites might be ascribed to the combined stimulus exhibited by the FP brain injury and the cell implantation (Molcanyi 2009). …”
Section: Inflammatory Responsementioning
confidence: 98%
See 1 more Smart Citation
“…Macrophage infiltration was shown to be less pronounced when stem cells were implanted into completely intact healthy brains. We therefore suggested that the massive macrophage infiltration at graft sites might be ascribed to the combined stimulus exhibited by the FP brain injury and the cell implantation (Molcanyi 2009). …”
Section: Inflammatory Responsementioning
confidence: 98%
“…As we believe, the tumorigenic fraction of implanted graft may have been scavenged by activaed macrophages, alongside with concomitant survival of stem cells turning into healthy neural phenotypes. Great caution is needed when stem cells are implanted in experimental settings of diseases associated with inflammatory response (such as stroke or traumatic brain injury) as the tumorigenic threat may stay unveiled (in case tumorigenic fraction is being removed by activated immune cells) (Molcanyi 2009). …”
Section: Tumor Formationmentioning
confidence: 99%
“…The open chromatin conformation seen at multiple promoter regions in ES cells also suggests the rationale for open chromatin structure in stem cells. Adults stem cells are also a potentially safer cell source, compared to embryonic stem cells, which are known to form teratomas, a specific type of tumour consisting of derivatives of all three germ layers when implanted into ectopic sites [49,50]. This effect has not been reported following implantation of adult stem (progenitor) cells.…”
Section: Epigenetics and Stem Cell Biologymentioning
confidence: 99%
“…However, compared to embryonic stem cells (ESCs), adult stem cells such as Other potential advantages of MSCs are a lower probability of tumor formation compared to ESCs, and their ability to be transplanted across allogeneic barriers (Trzaska et al (2009), Mohseny et al (2009), Molcanyi et al (2009) ). The latter provides MSCs with a major advantage since these cells could be immediately available as an offthe-shelf source.…”
Section: Introductionmentioning
confidence: 99%